The Macleaya cordata Symbiont: Revealing the Effects of Plant Niches and Alkaloids on the Bacterial Community - Lei, Fangying; Liu, Xueduan; Huang, Haonan; Fu, Shaodong; Zou, Kai; Zhang, Shuangfei; Zhou, Li; Zeng, Jianguo; Liu, Hongwei; Jiang, Luhua; Miao, Bo; Liang, Yili (Frontiers in Microbiology, 2021)
Endophytes are highly associated with plant growth and health. Exploring the variation of bacterial communities in different plant niches is essential for understanding microbe-plant interactions. In this study, high-throughput gene sequencing was used to analyze the composition and abundance of bacteria from the rhizospheric soil and different parts of the Macleaya cordata. The results indicated that the bacterial community structure varied widely among compartments. Bacterial diversity was observed to be the highest in the rhizospheric soil and the lowest in fruits. Proteobacteria, Actinobacteria, and Bacteroidetes were found as the dominant phyla. The genera Sphingomonas (∼47.77%) and Methylobacterium (∼45.25%) dominated in fruits and leaves, respectively. High-performance liquid chromatography (HPLC) was employed to measure the alkaloid content of different plant parts. Significant correlations were observed between endophytic bacteria and alkaloids. Especially, Sphingomonas showed a significant positive correlation with sanguinarine and chelerythrine. All four alkaloids were negatively correlated with the microbiota of stems. The predicted result of PICRUST2 revealed that the synthesis of plant alkaloids might lead to a higher abundance of endophytic microorganisms with genes related to alkaloid synthesis, further demonstrated the correlation between bacterial communities and alkaloids. This study provided the first insight into the bacterial community composition in different parts of Macleaya cordata and the correlation between the endophytic bacteria and alkaloids.